(untitled) (Research, Society and Development, 2021)
Objective: to systemize available evidence in literature on the experience of the puerperium for the families. Methodology: an integrative review in databases: Medical Literature Analysis and Retrieval System Online, Cumulative Index to Nursing & Allied Health Literature, Web of Science, Scopus, Scientific Electronic Library Online and ScienceDirect as well as in the Virtual Health Library. In databases and researched, gates was done the crossing using the descriptors and keywords: families, family relationship, family relation, family dynamic, postpartum period, puerperium, postpartum, postpartum women, housing, domicile, domicile, domestic, apartment, apartments, house, houses, home, homes, dwelling, dwellings, life change events, experience, life. Results: the sample was constituted by eight articles that present cultural values transmitted generation by generation to other, that influence the family in the parenting of new members; the improvement of family relationship by practicing physical exercises by the women in puerperium; the use of social medias and the tools: Calgary Model of Family Assessment, Calgary Family Intervention Model and Newborn Behavioral Observation, to support the professional practice evidence based. Final considerations: the life cycle transitions, although makes part of the familiar development process, are generally accompanied by striking conflicts. The transformations occurred in puerperium, specifically, affect the family dynamic, requiring of health professionals, mainly nurses, support for adaptation to the new reality.